Model Pengembangan Media dalam Bimbingan Karier pada Siswa Sekolah Menengah Atas di Era Society 5.0 (Ulasan Penelitian di Indonesia pada Tahun 2019 – 2022) - Nurhayati, Novida; Purwoko, Budi (Da'wah Faculty of UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Career media development can help high school (SMA) students understand the various career options available, including information about educational requirements, job prospects, and job demands in various fields. This allows students to make more informed decisions about the career path they wish to pursue. This research aims to explain the development model (R&D) of career guidance media for high school students in the 5.0 era. This research provides students with better knowledge and helps them plan their careers. This research uses the library research method by providing references to track research results from time to time (Review of Research in Indonesia in 2019 – 2022). The results of this research show that the high school career counseling media model provides an assessment for future researchers so that they can create more creative and successful career counseling service media models in the future. In the 5.0 era, students must always uphold their abilities, talents, and intelligence. Developing career media for high school students is important to help students explore career options, build readiness, overcome uncertainty, and prepare themselves for their future. With the right access to relevant resources and information, high school students can make better decisions about the career path they want to pursue and develop concrete steps to achieve their career goals. Pengembangan media karir dapat membantu Siswa Sekolah Menengah Atas (SMA) memahami berbagai pilihan karir yang tersedia, termasuk informasi tentang persyaratan pendidikan, prospek pekerjaan, dan tuntutan pekerjaan di berbagai bidang. Hal ini memungkinkan siswa untuk membuat keputusan yang lebih terinformasi tentang jalan karir yang ingin ditempuh siswa. Penelitian ini untuk menjelaskan model perkembangan (R&D) media bimbingan karir siswa SMA di era 5.0. Penelitian ini untuk memberikan siswa pengetahuan yang lebih baik dan membantu dalam merencanakan karir masa depannya. Penelitian ini menggunakan metode library research dengan memberikan referensi untuk melacak hasil penelitian dari waktu ke waktu (Ulasan Penelitian Di Indonesia Pada Tahun 2019 – 2022). Hasil penelitian ini bahwa model media konseling karir SMA dan memberikan penilaian bagi peneliti selanjutnya agar dapat menciptakan model media layanan konseling karir yang lebih kreatif dan sukses di masa depan. Di era 5.0, peserta didik harus senantiasa menjunjung tinggi kemampuan, bakat, dan kecerdasannya. Pengembangan media karir bagi siswa SMA penting untuk membantu siswa menjelajahi pilihan karir, membangun kesiapan, mengatasi ketidakpastian, dan mempersiapkan diri untuk masa depannya. Dengan akses yang tepat ke sumber daya dan informasi yang relevan, siswa SMA dapat membuat keputusan yang lebih baik tentang jalan karir yang ingin ditempuh dan mengembangkan langkah-langkah konkret untuk mencapai tujuan karirnya.